Uniform versus Nonuniform Scaling of Normal Modes Predicted by Ab Initio Calculations: A Test on 2-(2, 6-Dichlorophenyl)-N-(1, 3-thiazol-2yl) Acetamide. (10th July 2014) - Srivastava, Ambrish K.; Pandey, Anoop K.; Pandey, Saurabh; Nayak, Prakash S.; Narayana, B.; Sarojini, B. K.; Misra, Neeraj
Abstract : A test on calculated vibrational modes of 2-(2, 6-dichlorophenyl)-N-(1, 3-thiazol-2yl) acetamide using ab initio density functional method has been performed. The calculated harmonic vibrational frequencies are scaled via two schemes, uniform, ν scaled = 0.9648 ν calculated, and nonuniform, ν scaled = 22.1 + 0.9543 ν calculated . Scaled vibrational modes are compared with experimental FTIR bands. A good correlation is shown between scaled frequencies with the correlation coefficient, R 2 = 0.99638 - 0.99639 . This clearly shows that both schemes efficiently reproduce observed spectrum. However, a close investigation of individual normal modes reveals that nonuniform scaling performs much better than uniform scaling especially in the high frequency region.